Loss of functional autonomy in medication management after start of therapy in older patients with haematological malignancies - Velghe, Anja; Noens, Lucien; De Buyser, Stefanie; Demuynck, Rein; Petrovic, Mirko (European Journal of Oncology and Environmental Health, 2016)
Purpose: Guidelines on older cancer patients recommend a comprehensive geriatric assessment, preferably including an item on medication management since cancer treatment further increases risks of polypharmacy. So far, little attention is given to non-adherence due to functional changes. We aimed to assess autonomy in medication management after start of therapy in older patients with haematological malignancies. In case of deterioration, we aimed to search for predetermining factors.Methods: Longitudinal single centre cohort study in patients ≥ 70 years.  Patients underwent a geriatric evaluation before and two months after start of therapy. Medication was registered both times.Results: Sixty two patients, median age 77 years, were included. At baseline 49 patients (79%) took their long-term medication independently. Independent medication management was significantly higher in patients taking